Monitoring biotransformations in polyesters - O'Neill, Jaime Alexandre Antunes (2004)
This paper describes two methods to monitor esterase hydrolysis at the surface of polyester fibres (PET-Polyethylene terephthalate). The hydroxyl groups were determined on the fibre surface by alkaline reaction with a reactive dye (CI Reactive Black 5) and colour intensity was determined using a reflectance spectrophotometer. The terephthalic acid solution formed was also quantified after reaction with peroxide by fluorimetric determination of the resulting hydroxyterephthalic acid. Detailed descriptions of those methods are given in this paper.